Pengaruh konseling laktasi terhadap pengetahuan, kemampuan dan keberhasilan ibu dalam pemberian ASI - Anita Liliana; Elsi Dwi Hapsari; Wenny Artanti Nisman (Berita Kedokteran Masyarakat (BKM), 2017)
The effect of lactation counseling towards mother’s knowledge, ability and success rate in breastfeedingPurposeThis study aimed to identify the effect of lactation counseling towards mother’s knowledge, ability, and success in breastfeeding in Panembahan Senopati General Hospital, Bantul.MethodsThis research was a quasi-experimental study with a post test-only non-equivalent control group design. Sample collection technique used consecutive sampling with 32 respondents as total samples in each group (intervention group and control group). ResultsBivariate analysis used chi square tests with significance level p<0.05.  The intervention group was given lactation counseling (p = 0.000 [<0.05]). There was a significant difference in mother’s ability to breastfeed between the intervention group and control group after they were given lactation counseling (p=0.012 [<0.05]; RR=1.917). There was also a significant difference in the success rate of breastfeeding between the intervention and control group after counseling (p= 0.006 [<0.05]; RR=2.500).ConclusionLactation counseling can positively affect the mother’s knowledge, ability, and success rate in breastfeeding.